2008
DOI: 10.1007/s11240-008-9375-z
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term time course studies of turmeric (Curcuma longa L.) microrhizome development in vitro

Abstract: Turmeric (Curcuma longa L.) plantlets were cultured in MS (Murashige and Skoog Physiol Plant 15:473-497, 1962) liquid medium with 6% sucrose. Microrhizome development was observed in the presence of methyl jasmonate (MeJa) (0, 5 and 16 lM) and benzyladenine (BA) (0, 0.32 and 1 lM). Leaf, root, rhizome growth, and sugar use were measured weekly for 6 weeks in small vessels (180 ml) and four times in 23 weeks in larger vessels (2.5 l). MeJa reduced leaf, root, and rhizome biomass. BA had a positive effect on bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Cousins et al [12] found that the rhizomes of turmeric ( C. longa ) have higher relative dry weight (dry weight/fresh weight) values than other organs, indicating an active accumulation of carbohydrates in these storage organs. The authors also found a linear relationship between dry weight and sugar use and suggested that this information will be useful in the development of a model for the conversion of sugars into biomass and subsequently into secondary metabolites [36]. Appropriate PGR treatments can increase the total sugar content of some fruits [37] and may influence the source/sink balance in the plant, resulting in an increase in the rate of carbohydrate accumulation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Cousins et al [12] found that the rhizomes of turmeric ( C. longa ) have higher relative dry weight (dry weight/fresh weight) values than other organs, indicating an active accumulation of carbohydrates in these storage organs. The authors also found a linear relationship between dry weight and sugar use and suggested that this information will be useful in the development of a model for the conversion of sugars into biomass and subsequently into secondary metabolites [36]. Appropriate PGR treatments can increase the total sugar content of some fruits [37] and may influence the source/sink balance in the plant, resulting in an increase in the rate of carbohydrate accumulation [19].…”
Section: Discussionmentioning
confidence: 99%
“…They are convenient for packing and transport, besides aiding in germplasm conservation and exchange. Cousins and Adelberg (2008) also reported that liquid media was more effective for mr induction, which can lead to cost reduction of gelling agent. Though this technology has to be cost-sensitive for commercial viability, no precise information is available on the cost reduction involved.…”
Section: Microrhizomesmentioning
confidence: 95%
“…However, incubation under fully dark condition was found to be favorable (Shirgurkar et al, 2001). Cousins and Adelberg (2008) used methyl jasmonate up to 0.45 mg/l along with BA (up to 0.45 mg/l) for induction of mr. Meja reduced root and rhizome biomass and BA had a positive effect on biomass accumulation. Shirgurkar et al (2001) and Peter et al (2002) observed induction of mr on media containing BA alone, while Rajan (1997) reported a combination of BA and NAA along with low levels up to 0.5 mg/l of ancymidol for the same effect.…”
Section: Microrhizomesmentioning
confidence: 99%
“…On the contrary, N2 had more growth than others. As turmeric is one of the row crops, the finger direction and the number of fingers depend on it [21]. In node-1, an average flex sensor resistance relating to the finger growth had been calculated as 3.96 cm/kΩ.…”
Section: Nodementioning
confidence: 99%